Politeness Strategies by "Ellie" from the Tv series "The Last of Us." - Agast Dwipayana, I Gede; Gede Irwandika (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2024)
This research thoroughly explores the captivating world of politeness strategies employed by the main character, "Ellie," in the immensely popular television series "The Last of Us." the data source was meticulously collected from the HBO streaming service website and a comprehensive transcript repository. Employing Brown and Levinson's politeness strategy framework (1987), the study embarked on a qualitative method analysis, carefully examining the dialogue and interactions of "Ellie" throughout the series. The investigation unravels a fascinating array of insights, shedding light on how "Ellie" masterfully employs diverse politeness strategies in her communications. The study identified 16 instances of various politeness strategies found within the series. Among these, the most frequently observed strategy was the "Bald on Record" approach, utilized a remarkable nine times (comprising 52.25% of the instances). Following this, the "Negative Politeness" tactic emerged with four occurrences (25%), while "Positive Politeness" was deployed twice (12.5%). Lastly, the "Off-record" strategy was observed once (10%). The findings of this research unveil a compelling pattern of "Ellie" consistently employing a wide range of politeness strategies throughout the series. It is intriguing that the prevalence of "Bald on Record" may be attributed to the dangerous and challenging circumstances Ellie and the other characters face in the post-apocalyptic world. Direct communication is a pragmatic approach in such dire situations, minimizing misunderstandings and saving precious time. This study's nuanced exploration of politeness strategies in "The Last of Us" offers valuable insights into the complexities of human communication, even in the face of adversity. It mirrors real-life communication challenges and strategies in diverse contexts.